2005
DOI: 10.1111/j.1464-5491.2005.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of specific congenital abnormalities in offspring of women with diabetes

Abstract: These data indicate that pre-gestational maternal diabetes is associated with strong teratogenic effects on the kidney, urinary tract, and heart, and strongly associated with multiple congenital abnormalities. We found no material association between diabetes and spinal congenital abnormalities and limb deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 26 publications
4
73
0
4
Order By: Relevance
“…By appropriate treatment of conditions like diabetes mellitus and infectious diseases of genital organs, embryopathies, preterm births and abortions could be prevented. [5,6] In our study, iron, folicacid, calcium and vitamins were the most frequently used drugs in pregnancy, with an average of 1.73 to 2.89 drugs per pregnant women. Phenobarbitone, isoxsuprine, progesterone, paracetamol, NSAIDs, antibiotics, anti-emetics, proton pump inhibitors/H2 blockers, antacids and antihypertensive drugs (nifedipine, methyldopa) were the other commonly used drugs.…”
Section: Discussionmentioning
confidence: 99%
“…By appropriate treatment of conditions like diabetes mellitus and infectious diseases of genital organs, embryopathies, preterm births and abortions could be prevented. [5,6] In our study, iron, folicacid, calcium and vitamins were the most frequently used drugs in pregnancy, with an average of 1.73 to 2.89 drugs per pregnant women. Phenobarbitone, isoxsuprine, progesterone, paracetamol, NSAIDs, antibiotics, anti-emetics, proton pump inhibitors/H2 blockers, antacids and antihypertensive drugs (nifedipine, methyldopa) were the other commonly used drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal diabetes has been associated with CHDs [24] and a clear link is shown between glycemic control during organogenesis and congenital malformations [26]. A number of studies have demonstrated a positive association between maternal obesity and CHDs as well [36,38], although others reported contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Of those congenital malformations that are seen in offspring of pregestational maternal diabetes, renal malformations such as renal agenesis and congenital abnormalities of kidney and urinary tract are most prevalent. 5 Renal morphogenesis involves complex events in which many genes interact to coordinate the formation of the final kidney. Abnormalities occur when the normal pattern of nephrogenesis is interrupted.…”
mentioning
confidence: 99%